Mutations in COQ4, an essential component of coenzyme Q biosynthesis, cause lethal neonatal mitochondrial encephalomyopathy. Issue 9 (16th July 2015) - Chung, Wendy K; Martin, Kimberly; Jalas, Chaim; Braddock, Stephen R; Juusola, Jane; Monaghan, Kristin G; Warner, Barbara; Franks, Samuel; Yudkoff, Marc; Lulis, Lauren; Rhodes, Roy H; Prasad, Vinay; et al.
Abstract : Background: The identification of the molecular basis of mitochondrial disorders continues to be challenging and expensive. The increasing usage of next-generation sequencing is facilitating the discovery of the genetic aetiology of heterogeneous phenotypes associated with these conditions. Coenzyme Q10 (CoQ10 ) is an essential cofactor for mitochondrial respiratory chain complexes and other biochemical pathways. Mutations in genes involved in CoQ10 biosynthesis cause primary CoQ10 deficiency syndromes that can be treated with oral supplementation of ubiquinone. Methods: We used whole exome sequencing to evaluate six probands from four unrelated families with clinical findings suggestive of a mitochondrial disorder. Clinical data were obtained by chart review, parental interviews, direct patient assessment and biochemical and pathological evaluation. Results: We identified five recessive missense mutations in COQ4 segregating with disease in all four families. One mutation was found in a homozygous state in two unrelated Ashkenazi Jewish probands. All patients were female, and presented on the first day of life, and died in the neonatal period or early infancy. Clinical findings included hypotonia (6/6), encephalopathy with EEG abnormalities (4/4), neonatal seizures (3/6), cerebellar atrophy (4/5), cardiomyopathy (5/6) and lactic acidosis (4/6). Autopsy findings in two patients revealed neuron loss and reactive astrocytosis or cerebellar and brainstem hypoplasia and microdysgenesis. Conclusions: Mutations in COQ4 cause an autosomal recessive lethal neonatal mitochondrial encephalomyopathy associated with a founder mutation in the Ashkenazi Jewish population. The early mortality in our cohort suggests that COQ4 is an essential component of the multisubunit complex required for CoQ10 biosynthesis.